(untitled) (Oxfordshire, UK, 2004)
This title has two volumes that provide a broad overview of our current knowledge of nematology. The first volume addresses basic biology, while the second covers applied aspects of nematodes as parasites or disease vectors, and the control of pest nematodes
Keywords: Nematoda,Plant nematodes,Soil nematodes